Indústria de suco de laranja integral - Pereira, Isabella Bordinhão Torres (2018)
The search for healthier habits has driven the human being to consume more food without preservatives and chemical additives. This demand has made the juice industry, especially integral ones, received prominence. Brazil, as a major producer and exporter of oranges, has in its intern market countless brands of juice. However, in the niche of the integrals, few industries bet, due to their shorter expiration date. The State of São Paulo is responsible for about 70% of the national orange harvest, with the Citrus Belt in its territory, which favors the implementation of an orange juice industry. Citrino, the company proposed in this work will be located in Franca - SP, due to owning the best water treatment in Brazil, providers around it within a maximum radius of 380 km and proximity to Santos’ port, in order to enter on the export market of frozen orange juice concentrate in the future. From the mass and energy balances it was possible to size the equipment used in the operational plant of Citrino, as well as to realize the energy integration in order to reduce the combustible material used in the boiler. The investment required to make this project possible will be returned after 3 years of factory operation. Concerned about the environment, Citrino proposes to carry out activities that have a minimal impact on the environment, such as collecting rainwater for later non-potable use in its facilities, efficiently treating effluents, and donating orange peel and bagasse for feed producers.